Deklamation im antiken Theater und im 18. Jahrhundert. Die Re-Interpretation von Melopoie und Rhythmopoie durch Abbé Dubos und Gotthold Ephraim Lessing - Meyer-Kalkus, Reinhart (Hyperboreus, 2015)
Following a dogma of French theatre in the 17th and 18th century, the declamation of metrically regulated verses on stage (for example in tragedies of Corneille, Racine and Voltaire) had to be distinct from any feature of a day to day communication. The artiﬁcial speech of High Tragedy (discours artiﬁciel) was not to be confounded with ordinary speech (discours naturel). Abbé Dubos, one of the most inﬂuential writers of aesthetic theory in the ﬁrst half of the 18th century, defended the argument that this kind of declamation, practiced by French actors on the contemporary stage, was already used by ancient actors of Greek tragedy. This argument was heavily contested by a whole generation of theatre critics and philosophers in the second half of the 18th century, among them Gotthold Ephraim Lessing who claimed that the declamation of the Greek actors had nothing to do with the speciﬁc French style of classicist declamation. In contrast, he elaborated a concept of a natural style of declamation, primarily founded on a natural rhythm of speech, which lends itself to immediate sympathy (Mitleid).